Automation and Modernization of Meteorological Observation Network in Nigeria - A. Hussaini; S.O. Yakubu (Journal of Applied Sciences and Environmental Management)
In Nigeria the beginning of automation of meteorological parameters was dated back to 1998 when five Automatic Weather Observation Systems (AWOSs) were installed at different locations. Unfortunately we were unable to sustain those equipment due to low literacy level of most operational staff available at the time of implementation. The Nigerian Meteorological Agency (NIMET) is making frantic efforts to ensure provision of timely and accurate Weather Information through acquisition of weather monitoring systems and training of technical and operational personnel on data capturing and data dissemination systems. In year 2006, NIMET embarked on installation of Automated Weather Observing Systems at four international airports namely Abuja, Lagos, Kano and Port Harcourt respectively. In 2009 additional Aviation Automated Weather Observing Systems (AWOS) at six other Airports such as Ilorin, Enugu, Owerri, Calabar, Katsina and Maiduguri were installed. Today, all synoptic stations in various location in Nigeria have AWOS installed.